Adolescents’ Lived Experiences of COVID-19 - Layton, Kirstyn; Jacobs, Issie (Ревија за социјална политика/Journal of Social Policy, 2024)
Adolescents experienced COVID-19 and the implementation of lockdown measures in various ways. The developmental phase of middle adolescence is a pivotal period characterised by various cognitive and social processes that contribute significantly to the creation of adolescents’ identity. During this period, adolescents encounter significant events, both in terms of their personal growth and their lived experiences. These events may include transitioning to high school, obtaining their learner’s licences, and other milestones. The implementation of lockdown measures and stay-at-home orders resulted in adolescents being restricted to their residential settings with their family members. Understanding adolescents’ lived experiences of COVID-19 was described through a qualitative phenomenological descriptive research design. The data collection consisted of individual semi-structured interviews with 16 participants in Johannesburg (Gauteng), using an interview schedule. The data was analysed using thematic content analysis and three themes emerged: (1) Participants’ experience of how COVID-19 Influenced their relationships, (2) Participants’ experience of how COVID-19 impacted their mental health, and (3) Protective factors and risk factors that impacted their experience of COVID-19 positively or negatively. From this, conclusions have been drawn, as well as recommendations for future research and practice. Initiatives that can potentially be used to support adolescents during a crisis period, such as a pandemic, include interventions related to mental health, academic performance, and physical well-being.